Habits Related to Strength Training of Brazilian Recreational Runners - Wagner K. A. Santos; Lucas D. M. Forte; Alexandre S. Silva; Hallisson V. de O. Rufino; Lucas de F. Vieira; João M. F. Lima Silva; Mabliny Thuany; Reginaldo Gonçalves; Ytalo M. Soares (Sports)
Despite strength training (ST) being well characterized by professional runners, little is known about the inclusion of ST models for recreational runners. Thus, the present study aimed to investigate the presence of ST in the training practices of recreational runners, with a focus on understanding its characteristics and the motivations of recreational athletes for including ST in their routines. To this end, 801 recreational runners (493 male and 308 female) completed a structured questionnaire regarding their training habits, the inclusion of ST, and its characteristics, concerning the type of ST, training volume, and the reasons for including ST in their training programs. To assess the possible associations between categorical variables, data were analyzed using the chi-square test for independent samples. Approximately 625 runners (78.1%) reported that they included ST in their training routine, with a statistically significant difference between the sexes (men: 73.5% vs. women: 85.4%; X2 = 14.09; p = 0.01). Traditional strength training (TST) was the predominant type of ST included (78.5%), with most participants performing 2–4 sets and 8–12 repetitions per set at a frequency of 3–4 sessions per week. The importance of ST was primarily attributed to performance improvement (85%). The results suggest that recreational runners incorporate different types of ST into their training routines, with TST being the predominant type perceived by runners as a valuable asset for improving running performance.